History of the world for young readers - Gelinas, Paul J. (New York : Grosset & Dunlap, 1965)
A history of the world from prehistoric man to the space age discussing man's discoveries and inventions and the growth of civilization.
includes index.
Keywords: World history -- Juvenile literature; World history